DYNAMICS OF CHANGES IN NITROGEN OXIDE DERIVATIVES IN YOUNG PATIENTS WITH GASTROESOPHAGEAL REFLUX DISEASE - Gorodnytska, I.M.; Skrypnyk, I.M.; Maslova, G.S. (World of Medicine and Biology, 2025)
urrent research is devoted to studying the role of nitric oxide and NO synthase in ensuring the functioning of the gastrointestinal tract. The work aims to study the importance of the role of nitric oxide in the pathogenesis of gastroesophageal reflux disease to analyze the clinical symptoms and state of endothelial dysfunction of the esophageal mucosa depending on the variant of the disease course by determining the concentration of nitric oxide derivatives and levels of NO-synthase activity. The results obtained by us indicate an increase in the level of inflammatory markers in young patients regardless of the presence of erosive lesions of the esophageal mucosa. Further studies are needed to assess the selective effect of NO-synthase isoforms to determine their role in the management and treatment of patients with gastroesophageal reflux disease at a young age.